Framework of Quality Assurance of TEL Integration Into an Educational Organization - Volungeviciene, Airina; Teresevičienė, Margarita; Tait, Alan William (International Review of Research in Open and Distributed Learning, 2014)
This research paper addresses the issues of integration of technology enhanced learning (TEL) into an educational organization. Good practice experience cannot be directly transferred to new organisations due to different contextual conditions. The TEL integration depends significantly upon a very rapid development of services and information communication technologies (ICT). Some organizations have managed to go step by step with the developments and have become leaders in TEL provision, however others, though having successful examples, have not succeeded in reaching the service level they want. While many positive examples exist in research literature, it is rare that institutions have complete strategies or solutions for integrating TEL that meet their specific pre-conditions and satisfy quality assurance parameters at the same time. The research reported here aims at the development of a theoretical framework for quality assurance of TEL integration into educational organizations. During the research, the development of the TEL concept has been discussed, success indicators for TEL integration in an educational organization have been described, the quality parameters of TEL integration into an educational organization have been identified and the model for TEL integration into an organization has been developed.